LEARNING FOREIGN LANGUAGES THROUGH THE TELETANDEM PROJECT - Erkaboyeva S. Y. (Galaxy International Interdisciplinary Research Journal, 2022)
In learning a foreign language, it is important to have the learners ’interest in learning the language and the learners’ desire to learn the language, as well as to motivate, inspire and motivate the learners to learn the language. In this article, we want to share a Teletandem language learning project between a group of Japanese students and students of our institute. Teletandem is an effective and efficient way to learn a foreign language, which allows participants to gain self-confidence, time management, deepen the study of the language culture through language learning and free thinking. Teletandem is one of the most effective motivational methods that serves to develop expressiveness.